Mechanical behavior of injection-molded starch-based polymers - Reis, R. L. (1996)
This work evaluates the mechanical performance of injection-molded starch-based copolymers, 60/40 (mol/mol) starch/poly(ethylene vinyl alcohol), and the possibility of improving material properties through deliberately induced anisotropy during processing. Different types of samples were produced by conventional and shear-controlled injection molding (Scorim) and tested under tensile and impact loading. The behavior of three distinct grades is discussed in terms of the respective fracture morphology (evaluated by scanning electron microscopy). A comparison is made between the behavior of conventional and Scorim samples. The results show that the mechanical properties of the materials used were significantly improved by the employment of the Scorim process. The stiffness values of the conventional moldings were doubled, without reducing the ductility of the polymer. The impact data showed a material sensitivity, and consequent loss of properties, to the localized shear imposed to the melt during processing. This situation is attributed to very narrow mold gates (in the case of pingated systems) and leads to much reduced impact performance.